Pengaruh Suku Bunga Acuan Terhadap Harga Saham Bank Mandiri Pada Tahun 2013-2020 - Ah. Syahril Qisthi; Tony Seno Aji (Jurnal Ekonomika : INDEPENDEN, 2022)
Abstract The purpose of this study is to analyze the effect of bencmark interest rates on the stock price of Bank Mandiri in Indonesia to helps investors obtain maximum returns. The research approach uses a quantitative paradigm with a simple linear regression analysis tool. The data used are secondary data obtained through the documentation method. The results of the study indicate that the interest rate variable has an effect on stock prices. The value of fluctuating interest rates determines investors to invest their capital, the higher the interest rate, the higher the share price of Bank Mandiri.